1994
DOI: 10.1029/94wr01788
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional analysis of infiltration from the disc infiltrometer: 2. Physically based infiltration equation

Abstract: Abstract. In situ measurement of soil hydraulic properties may be achieved by analyzing the unconfined effiux from disc tension infiltrometers, once consistent infiltration equations can be derived. In this paper an analytical, three-dimensional infiltration equation is developed, based on the use of parameters with sound physical meaning and adjustable for varying initial and boundary conditions. The equation is valid over the entire time range. For practical purposes, a simplified solution is also derived. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
416
4
31

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(512 citation statements)
references
References 14 publications
5
416
4
31
Order By: Relevance
“…Conversely, the second term dominates as time increases, subject to the limit of t ¼ S 2 /C 2 , when the series expansion from which equation (1) was derived is no longer accurate. Alternate expressions have been developed to describe long-time (steady-state) infiltration behavior [Philip, 1957a[Philip, , 1957bWooding, 1968;Haverkamp et al, 1994], which lend themselves to estimations of K s . However, the time required to reach late-time or quasi-steady state conditions may be impractical, particularly for soils with low hydraulic conductivity, and assumptions of homogeneity are typically violated for long infiltration experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the second term dominates as time increases, subject to the limit of t ¼ S 2 /C 2 , when the series expansion from which equation (1) was derived is no longer accurate. Alternate expressions have been developed to describe long-time (steady-state) infiltration behavior [Philip, 1957a[Philip, , 1957bWooding, 1968;Haverkamp et al, 1994], which lend themselves to estimations of K s . However, the time required to reach late-time or quasi-steady state conditions may be impractical, particularly for soils with low hydraulic conductivity, and assumptions of homogeneity are typically violated for long infiltration experiments.…”
Section: Introductionmentioning
confidence: 99%
“…One uncertainty shared by both surface mounted ring and disk infiltrometers is the time variant diameter of the wetting front in the subsurface, which is governed by capillary diffusivity in highly sorptive soils and distorted by macropores and cracks in dual permeability media at high positive heads (Haverkamp, Ross, Smettem, & Parlange, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that Wooding's approach will overestimate the soil hydraulic conductivity if steady-state infiltration is not reached. Discrepancies between tension infiltrometer and other methods in practice, however, are caused probably more by variability within each method such as soil heterogeneity or simplification of the hydraulic conductivity function to an exponential expression, than by inherent limitations of the steady-state solutions (Wang et al, 1998 (Warrick, 1992;Haverkamp et al, 1994;Zhang, 1998) have in common the following two-term form of the cumulative infiltration equation:…”
Section: Tension Disc Infiltrationmentioning
confidence: 99%
“…Haverkamp et al (1994), for example, posed the following physically based expressions valid for times not approaching steady-state:…”
Section: Tension Disc Infiltrationmentioning
confidence: 99%